Utilization of Statins, an HMG-CoA reductase inhibitors, in Ambon District Hospital, Maluku: a retrospective study - Simatupang, Abraham; Huningkor, Yusuf; Gasperz, Westi C; Nindatu, Maria; Noya, Farah; Sanaky, Marliyati; Hutagalung, Inggrid; Yolanda, Denny; Kailola, Natalie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Non-infectious diseases, including hypercholesterolemia, are now ranked top 10 inIndonesia. Statins are inhibitors of HMG-CoA reductase, an enzyme for biosynthesis ofcholesterol in the liver. Statins have been proven to reduce the risk of death due to CHDand mortality from various reasons. The objective of the study is to know the utilizationof statins in peripheral area of Indonesia. This retrospective study on utilization of statinsprescribed for hypercholesterolemia was taken from medical record year of 2014-2015of a District Hospital – Dr. Haulussy, Ambon, and Maluku. We collected demographicdata, pre- and treated concentrations of total cholesterol (TC), low-density lipoproteincholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglyceride (TG),types and dosages of statins or other lipid-lowering medications given. Student t-testusing was performed to check statistical differences for all cholesterol and TG differencesprior to therapy versus during treatment. Eighty three respondents consisted of 26 men(31.3%) and 57 women (68.7%) with mean age 60 ± 11 years old. The pre-treatment/post-treatment values (mg/dL) of TC: 245.22 ± 51.40/224.97 ± 98.79 (p=0.004);LDL-C: 166.07 ± 45.36/146.00 ± 41.07; HDL-C: 54.52 ± 37.95/43.00 ± 0.00; andTG: 177.36 ± 103.25/121.00 ± 52.87, respectively. Seventy-nine patients (95.2%)were treated with statins. The dosage given were 10 mg (n=19, 22.9%), 20 mg (n=63, 75.9%), and 40 mg (n=1, 1.2%). Twenty-eight patients (33.7%) had no posttreatmentdata of cholesterol, and 31 out of 55 patients (56%) were responders. Allcholesterol levels were decreased, but responder rate was only 56%. Therefore, dosageadjustment and prerequisite cholesterol level during and post-treatment measurementshould be made regularly.